Genetic variability in biparental progenies of feed barley (Hordeum vulagre L.) under drought environment - Gopi Krishan Gaur; S.S. Punia (Annals of Agricultural Research, 2025)
The present investigation was carried out to study genetic variability parameters in bi-parental progenies of Barley (Hordeum vulgare L.) under drought condition. To achieve the objectives of present investigation F2 population of RD 2715 x RD 3002 were raised and backcross to both the parents according to North Carolina Design III (Biparental mating Design). Three random F2 plants as males and backcrossing them to both the original parents. Six progenies generated in this way make up one set and likewise, three sets were generated using random samples of plants in F2 population. BIPs of cross RD 2715 x RD 3002 under drought condition showed twelve high heritable characters with maximum was for days to maturity (88%). Additive variance due to male was greater than the females and average additive variance was greater than dominance variance indicating the predominant role of additive gene action in the inheritance of these characters.